Enhancement of organics and nutrient removal and microbial mechanism in vertical flow constructed wetland under a static magnetic field. (15th March 2023) - Li, Cong; Feng, Likui; Lian, Jianjun; Yu, Xiaoting; Fan, Chunzhen; Hu, Zhen; Wu, Haiming
Abstract: Low and unstable pollutant removal is regarded as the bottleneck problem in constructed wetlands (CWs) for wastewater treatment. This study investigated the effect of static magnetic field (MF) on enhancing the purification efficiency and microbial mechanism in vertical flow CW systems for treating domestic wastewater. The results showed that MF-CWs outperformed control systems in terms of treatment performance, with average removal efficiencies of COD, NH4 + -N, TN, and TP reaching 92.58%, 73.58%, 72.53%, and 95.83%, respectively. The change of malondialdehyde (MDA), catalase (CAT), and superoxide dismutase (SOD) activity indicated that MF application was beneficial for plant health. Additionally, higher ammonia monooxygenase (AMO) activity in MF-CWs suggested the removal of NH4 + -N was facilitated. The high-throughput sequencing results demonstrated that MF application could enrich the functional bacteria such as Patescibacteria phylum, mainly, including Gammaproteobacteria, Betaproteobacteria, and Alphaproteobacteria, which further accelerated pollutants transformation. These findings would be beneficial in understanding pollutant removal processes and their mechanism in CWs with MF application. Graphical abstract: Image 1 Highlights: Better treatment performance was achieved in constructed wetlands with magnetic field. Magnetic field was beneficial for the health of wetland plants. Magnetic field increased enzyme activity especially for ammonia monooxygenase. Functional bacteria of nitrogen enriched in magnetic field-based constructed wetlands.